Diagnostic imaging of shoulder rotator cuff lesions - Nogueira-Barbosa,Marcello Henrique (2002)
Shoulder rotator cuff tendon tears were evaluated with ultrasonography (US) and magnetic resonance imaging (MRI). Surgical or arthroscopical correlation were available in 25 cases. Overall costs were also considered. Shoulder impingement syndrome diagnosis was done on a clinical basis. Surgery or arthroscopy was considered when conservative treatment failure for 6 months, or when rotator cuff repair was indicated. Ultrasound was performed in 22 patients and MRI in 17 of the 25 patients. Sensitivity, specificity and accuracy were 80%, 100% and 90.9% for US and 90%, 100% and 94.12% for MRI, respectively. In 16 cases both US and MRI were obtained and in this subgroup statistical correlation was excellent (p< 0.001). We concluded that both methods are reliable for rotator cuff full thickness tear evaluation. Since US is less expensive, it could be considered as the screening method when rotator cuff integrity is the main question, and when well trained radiologists and high resolution equipment are available.